Density Functional Theory Study of Reaction Equilibria in Signal Amplification by Reversible Exchange. Issue 19 (22nd September 2021) - Lin, Kailai; TomHon, Patrick; Lehmkuhl, Sören; Laasner, Raul; Theis, Thomas; Blum, Volker
Abstract: An in‐depth theoretical analysis of key chemical equilibria in Signal Amplification by Reversible Exchange (SABRE) is provided, employing density functional theory calculations to characterize the likely reaction network. For all reactions in the network, the potential energy surface is probed to identify minimum energy pathways. Energy barriers and transition states are calculated, and harmonic transition state theory is applied to calculate exchange rates that approximate experimental values. The reaction network energy surface can be modulated by chemical potentials that account for the dependence on concentration, temperature, and partial pressure of molecular constituents (hydrogen, methanol, pyridine) supplied to the experiment under equilibrium conditions. We show that, under typical experimental conditions, the Gibbs free energies of the two key states involved in pyridine‐hydrogen exchange at the common Ir‐IMes catalyst system in methanol are essentially the same, i. e., nearly optimal for SABRE. We also show that a methanol‐containing intermediate is plausible as a transient species in the process. Abstract : Chemical exchange mechanisms in SABRE : Density functional theory calculations are used to analyze the detailed mechanisms and reaction energies of Signal Amplification by Reversible Exchange (SABRE). Theoretical calculations rationalize typical reaction conditions and indicate that the pyridine‐H2 exchange process on the Ir‐IMes catalyst follows a dissociative interchange mechanism. The presented framework can aid developments of new SABRE systems in the future.